A COMÉDIA NA POÉTICA DE ARISTÓTELES - Destrée, Pierre (Organon, 2010)
This paper tries to reconstruct what might have been Aristotle’s theory ofcomedy. Through the analysis of the actual text of the Poetics, along with some other textsof Aristotle, I draw conclusions regarding the nature of comedy and laughter in Aristotle’sthinking, and reflect upon subjects there implied, such as what would be the role played bykatharsis in comedy and the emotions proper to comedy.